Development of Multimedia-Assisted E-LKPD Based on Problem-Based Learning to Improve Mathematical Problem-Solving Abilities and Independent Learning of Junior High School Students - Khairunnisa’ Nabilah; Kms.Muhammad Amin Fauzi; E. Elvis Napitupulu (Jurnal Perspektif, 2026)
This study aims to develop a valid, practical, and effective multimedia-assisted problem-based E-LKPD (Electronic Student Worksheet) to improve mathematical problem-solving abilities and learning independence among junior high school students. In addition, this study analyzes improvements in students' mathematical problem-solving abilities through the use of the E-LKPD. The method used is development research with the ADDIE model, which was implemented at SMP Negeri 11 Medan. The research instruments include expert validation sheets, teacher and student response questionnaires, mathematical problem-solving ability tests, and learning independence questionnaires. The results of the study indicate that the developed E-LKPD meets the criteria of "Very Valid", "Practical", and "Effective", and has a significant effect on improving students' mathematical problem-solving abilities and learning independence. This is indicated by (a) the results of the paired-samples t-test with a significance value of 0.000 < 0.05, (b) the N-Gain value for mathematical problem-solving ability of 0.589, and (c) the N-Gain value for learning independence of 0.411, with the majority of students in the “Moderate” improvement category. Thus, the use of multimedia-assisted E-LKPD has been proven to be able to significantly improve students' mathematical problem-solving abilities.